Structural modal testing using a human actuator. (15th October 2020) - Han, Ziping; Brownjohn, J.M.W.; Chen, Jun
Highlights: Use humans as actuators for structure modal testing. Exciting force can be reconstructed by wearable sensors measurement and a single rigid body model. One engineer with two wearable sensors can finish the testing task. Abstract: The dynamic testing of as-built structures is essential for understanding structural dynamic properties, updating finite-element models, maximizing the effectiveness of structural performance monitoring, and planning vibration mitigation measures. Traditional dynamic test technologies using logistically challenging systems of mechanical actuators, sensors, and signal generation/acquisition instruments may not be feasible for the modal testing of low- to medium-rise buildings, which comprise the majority of commercial and residential buildings in cities. The human body, which is an intelligent dynamic system with advanced sensing and control abilities, has demonstrated excellent potential as an excitation source for structure vibration owing to individuals and crowds walking, jumping, bouncing, or swaying. The force generated by human activity can be maintained over a narrow frequency bandwidth and can reach significant amplitudes, readily generating the resonance response of structures with low natural frequencies. This study investigates the use of humans as actuators for structure modal testing. The application protocol is first proposed, and intelligent wearable sensors and force plates are used to calibrate humans as actuators. By modelling human as combination of rigid bodies, with an appropriate choice of mass participant ratio, the human exciting force can be well reconstructed using the acceleration measured by wearable sensors at featured body points. The application of the proposed protocol on a building with a typical frame construction and on a large span floor verified its suitability for estimating the modal frequency, damping ratio and modal mass with reasonable accuracy, thereby demonstrating the practicability of modal testing using human actuators.